Early OCT angiography changes of type 1 CNV in exudative AMD treated with anti-VEGF. Issue 1 (22nd March 2018) - Pilotto, Elisabetta; Frizziero, Luisa; Daniele, Anna Rita; Convento, Enrica; Longhin, Evelyn; Guidolin, Francesca; Parrozzani, Raffaele; Cavarzeran, Fabiano; Midena, Edoardo
Abstract : Aims: To investigate, with optical coherence tomography angiography (OCTA), short-term changes of type 1 choroidal neovascularisation (CNV), secondary to exudative age-related macular degeneration, after anti-vascular endothelial growth factor (VEGF) treatment. Methods: Patients affected by type 1 CNV treated with intravitreal anti-VEGF were consecutively enrolled. All patients underwent OCTA examination before and 48 hours after anti-VEGF treatment. Quantitative and qualitative vascular and morphological macular changes were evaluated. Results: Sixteen eyes were included (11 treated with aflibercept and 5 with ranibizumab). Both CNV mean area and pigment epithelium detachment significantly reduced (p=0.0004 and p=0.0007, respectively) after treatment. Cystoid macular oedema (four eyes) decreased in all cases. Neuroretinal detachment (13 eyes) decreased in 85% of cases (11 eyes). Fine CNV vessels density decreased in 75% (12 eyes), whereas larger CNV vessels density remained stable in 66.7% (10 eyes), choroidal flow void signal (7 eyes at baseline) increased in 42.9% (3 eyes) of them and remained stable in 57.1% (4 eyes). Interoperator reproducibility for OCT examination was good for all measurements (intraclass correlation coefficient>0.65). Conclusion: Early remodelling of type 1 CNV network after treatment may be non-invasively and reproducibly analysed by means of OCTA. Choroidal perfusion impairment, choroidal flow void signal, surrounding CNV may change during treatment.